PENILAIAN KARIR DAN PERENCANAAN KEHIDUPAN - Fauziah Fauziah; Islamezi Rizmi; Wahidah Fitriani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
There is a high demand in career assessment and life planning for standardized career assessments, especially with the increasingly sophisticated use of technology in counseling. Therefore, the aim of this study is to know and understand measures of career readiness, comprehensive assessment programs, and standard assessments. The type of research used is library research. The results of the literature research conducted revealed that career measurement can use various inventories. Furthermore, a number of computer-based career and life planning programs have been developed in recent years. There are several standard assessment programs, namely: ACT Career Planning Survey, Differential Aptitude Tests, WorkKeys, O*NET System and Career Exploration Tools, Career Occupational Preference System.